2011
DOI: 10.1007/s12307-011-0072-9
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis and Multiple Myeloma

Abstract: The bone marrow microenvironment in multiple myeloma is characterized by an increased microvessel density. The production of pro-angiogenic molecules is increased and the production of angiogenic inhibitors is suppressed, leading to an "angiogenic switch". Here we present an overview of the role of angiogenesis in multiple myeloma, the pro-angiogenic factors produced by myeloma cells and the microenvironment, and the mechanisms involved in the myeloma-induced angiogenic switch. Current data suggest that the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 137 publications
5
83
0
Order By: Relevance
“…[8][9][10] Aberrant angiogenesis has been reported in MM-infiltrated BM, [11][12][13] and increased angiogenic activity is associated with endothelial activation, increased capillary permeability, and hyperperfusion. [14][15][16] Evidence suggests that MM cells promote angiogenic activity via hypoxia-inducible factor (HIF)-1a, a key transcription factor of hypoxia, leading to the overproduction of angiogenic cytokines such as vascular endothelial growth factor (VEGF), 17 angiopoietin-1, 18 and osteopontin. 19 In addition to conventional signaling pathways responding to hypoxia (ie, direct cell-cell contact or VEGF signaling), 10 our group and others have shown that exosomes, small endosome-derived vesicles containing a wide range of functional proteins, mRNA, and miRNA, from hypoxic cancer cells help to modulate the microenvironment without contacting the surrounding noncancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Aberrant angiogenesis has been reported in MM-infiltrated BM, [11][12][13] and increased angiogenic activity is associated with endothelial activation, increased capillary permeability, and hyperperfusion. [14][15][16] Evidence suggests that MM cells promote angiogenic activity via hypoxia-inducible factor (HIF)-1a, a key transcription factor of hypoxia, leading to the overproduction of angiogenic cytokines such as vascular endothelial growth factor (VEGF), 17 angiopoietin-1, 18 and osteopontin. 19 In addition to conventional signaling pathways responding to hypoxia (ie, direct cell-cell contact or VEGF signaling), 10 our group and others have shown that exosomes, small endosome-derived vesicles containing a wide range of functional proteins, mRNA, and miRNA, from hypoxic cancer cells help to modulate the microenvironment without contacting the surrounding noncancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of these cells leads to secretion of factors that are of particular importance for the proliferation and survival of myeloma cells, especially IL-6, VEGF, and IGF-1, to the environment and intensification of chemotherapy resistance 8,9 . It has also been confirmed that factors such as basic fibroblast growth factor (bFGF), angiopoietin-1 (Ang-1), transforming growth factor beta (TGF-beta), platelet-derived growth factor (PDGF), hepatocyte growth factor (HGF), and interleukin 1 (IL-1), secreted by stromal cells of patients with MM, affect the growth of myeloma cells 10 . Recently, it has been reported that there is a novel mechanism of intercellular transfer of genetic information which involves stromal cell-derived exosomes, which, after entering myeloma cells, modulate their growth mediated by specific miRNAs 11 .…”
Section: The Role Of Endothelial Cells and Angiogenesismentioning
confidence: 99%
“…Angiogenesis, supporting the growth, survival, progression, and drug resistance acquisition of the MM cells, plays a critical role in the pathophysiology and progression of MM [54] . Hypoxia, a key feature of the most MM microenvironment, is a leading cause of angiogenesis [55] .…”
Section: Angiogenesis Repressionmentioning
confidence: 99%